Identification of a novel hypovirulence-inducing ourmia-like mycovirus from Fusarium solani causing ginseng (Panax ginseng) root rot - Ma, Kaige; Ni, Hechi; Liu, Zihang; Cai, Liping; Jiang, E.; Lu, Baohui; Yang, Lina; Zhang, Yanjing; Gao, Jie (Frontiers in Microbiology, 2025)
IntroductionFusarium solani is a widespread plant pathogen known to damage numerous crops, including causing severe root rot in Panax ginseng. In this study, we identified a novel ourmia-like mycovirus in F. solani, named “Fusarium solani ourmia-like virus 1” (FsoOLV1). We demonstrated that FsoOLV1 confers hypovirulence in its host F. solani and three other ginseng root rot pathogens, F. oxysporum, F. proliferatum, and F. verticillioides. Additionally, we verified its horizontal and vertical transmission capabilities.MethodsFsoOLV1 was discovered in F. solani strain SJH 2-4 using high-throughput sequencing. The genome sequence of FsoOLV1 was obtained through RT-PCR and RACE. Virus elimination was conducted to assess the effect of FsoOLV1 on fungal virulence. Protoplast transfection experiments were performed to evaluate the impact of the virus on other ginseng root rot pathogens. Horizontal and vertical transmission studies were also carried out to examine the spread of the virus.ResultsThe genome of FsoOLV1 is 2,801 nucleotides (nt) in length with a GC content of 47.05%. It encodes a 750 amino acid RNA-dependent RNA polymerase (RdRp), with a molecular weight of approximately 84.84 kDa. Phylogenetic analysis indicated that FsoOLV1 clusters within a clade containing the Magoulivirus genus in the Botourmiaviridae family. Curing FsoOLV1 from the fungal host strain revealed that the mycovirus plays a role in reducing the virulence of the F. solani strain SJH 2–4. Furthermore, protoplast transfection revealed that FsoOLV1 can significantly reduce the virulence of other ginseng root rot pathogens, including F. oxysporum, F. proliferatum, and F. verticillioides. Additionally, FsoOLV1 is capable of horizontal transmission between F. solani strains and vertical transmission to the next generation via conidia.DiscussionThis study presents the first hypovirulent ourmia-like virus, FsoOLV1, which reduces the virulence of F. solani and other ginseng root rot pathogens. Our findings suggest that FsoOLV1 could serve as a promising biological agent for controlling ginseng root rot. This research not only expands the diversity of known hypovirulent mycoviruses but also provides a potential candidate for controlling Fusarium diseases in ginseng cultivation.